The Implementation of Reading Strategies to Understand English Text: A Case Study of English Reading Class - Febrianti, Febby; Indica, Shelsa; Djuwita, Elly; Faishal Kusuma, Alwan; Sari, Puspita (International Journal of Psychosocial Rehabilitation, 2020)
Reading is not just pronouncing words. It requires understanding. Most experienced readers use a variety of strategies to understand text. Those strategies should be taught and applied to students in any different levels, starting from beginner until advanced learners. Teachers can, and should, teach some strategies to beginning readers in order to help students understand any text in any subject. This paper discusses how some reading strategies are implemented in understanding some English text. The reading skills strategies consist of Scanning, Previewing and Predicting, Understanding Vocabularies, Finding Topic, Stating Main Idea, and Supporting Details according to Mikulecky & Jeffries, 1996. This paper is aimed to find out (1) what reading strategies are the most difficult to be understood by the students and (2 )what is the impact of learning reading strategies through the students’ academic result. The respondents are the 2nd semester students of English Department who take Reading for Basic Strategies subject. The result shows that Finding Topic and Stating Main Idea is the most difficult reading strategies understood by the students. Some of them find difficulties to differentiate between identifying topic and determining main idea. The academic result at the end of the semester is mostly excellent. By implementing the reading skills strategies, students can answer the reading questions fast and correctly so that they can understand the English text effectively.